Heidegger und die Psychiatrie - Denker, Alfred; Groth, Miles; Jenewein, Josef; Zaborowski, Holger (Verlag Karl Alber, 2023)
This volume publishes the important correspondence between Martin Heidegger and Ludwig Binswanger and between Heidegger and Viktor Frankl. In essays by established experts, Heidegger's influence on psychiatry, psychology, psychotherapy, and existential analysis is discussed and his lasting significance for these disciplines is shown. Heidegger's thinking makes it possible to think deeply about health and illness, the human body or the doctor-patient relationship. For anyone interested in Heidegger's work, his way of thinking, the relationship between philosophy and medicine, or the question of human nature, this volume offers a wealth of new insights and stimulates an in-depth new dialogue across the boundaries of the disciplines.